History's Role in Coordinating Decentralized Allocation Decisions - Meyer, Donald J.; Van Huyck, John B.; Battalio, Raymond C.; Saving, Thomas R. (Journal of Political Economy, 1992)
What causes individual suppliers to allocate goods in such a way that the aggregate allocation satisfies the law of one price? A satisfactory answer to this question must confront two related problems: Equal net prices at all allocations provide no information to suppliers about the quantity to deliver to a specific location, and strategic uncertainty makes an observed violation of the law of one price an unreliable indicator of a profit opportunity. This paper develops a simple analytical framework to formalize these two problems, reviews some solutions found in the literature, and reports laboratory evidence on how people solve them. In addressing these issues, we focus on the role historical prices play in coordinating decentralized allocation decisions.